Solvent-free synthesis of a porous thiophene polymer by mechanochemical oxidative polymerization. Issue 44 (20th June 2018) - Grätz, S.; Oltermann, M.; Troschke, E.; Paasch, S.; Krause, S.; Brunner, E.; Borchardt, L.
Abstract : An oxidative polymerization reaction was brought into the solvent-free environment of a ball mill, yielding a porous polymer with a defined structure and high surface area. Abstract : This study elucidates a mechanochemical approach to synthesize a microporous thiophene polymer via oxidative polymerization. Utilizing a design of experiments approach we optimized the reaction conditions leading to complete conversion and a polymer with a surface area of up to 1850 m 2 g −1 – almost twice as high as the material prepared by solution-based polymerization. Thus, our approach presents a solvent free, quick and scalable alternative for the production of porous polymers.